“You Sleep, You Die”: A Rare Clinical Case of Ondine’s Curse after Posterior Fossa Surgery - Mitesh Karn; Basant Kumar Mahato; Ranjan Sah; Dipendra Kandel; Shabal Sapkota (Case Reports in Surgery)
Ondine’s curse is a rare condition in which breathing is preserved while awake, but there is absence of autonomic control of ventilation. It is a potentially fatal complication that may result rarely from surgery in posterior fossa in area close to respiratory centers. We describe a patient with posterior fossa hemangioblastoma who underwent subtotal resection via telovelar approach and developed acquired Ondine’s curse postoperatively. The patient’s presentation and management are described. Besides that, Ondine’s is a great example of how modern medicine is linked to ancient literature, and thus, its anecdotal history is also described.